Composite heat-conducting filler, graphene in-situ modified heat-conducting gel, preparation and application
By growing aluminum trioxide in situ on the graphene surface and using spray drying technology, thermal conductivity gels with high thermal conductivity coefficient and low specific surface area are prepared, which solves the problem of insufficient thermal conductivity of existing thermal conductivity gels and achieves efficient thermal conductivity Performance improvement and industrial applicability.
Patent Information
- Application Number
- CN202310794935.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
When existing thermal conductivity gels improve thermal conductivity, the large addition of thermally conductive particles will increase cost and weight, reduce interface wetting and viscosity, and make it difficult to significantly improve thermal conductivity.
A composite thermal conductivity filler with graphene oxide wrapped in aluminum trioxide was prepared by growing aluminum trioxide in situ on the graphene surface, combined with spray drying technology, a thermal conductivity gel with high thermal conductivity coefficient and low specific surface area was prepared.
The thermal conductivity reaches 8 to 12W/(m·K) and a high extrusion rate, which reduces the cost and weight of the material, and improves the interface wetting and viscosity, making it suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to a composite heat-conducting filler, a graphene in-situ modified heat-conducting gel, and preparation and application thereof. Background Art
[0002] In the process of device heat dissipation, heat needs to be transferred from the inside of the device through the device packaging material and the heat sink interface and then through the heat sink to the external environment. Because the solid surface is rough and uneven on a microscopic scale, even if the contact pressure between the two solid surfaces is as high as 10MPa, the actual contact area only accounts for 1-2% of the apparent contact area, and the rest is tiny pores filled with air. In order to reduce the interfacial thermal resistance, people have developed thermally conductive interface materials. Filling the interface thermal conductive material between the contact surfaces can remove the air in the pores of the contact interface, forming a continuous heat conduction channel on the entire contact interface, and improving the heat dissipation efficiency.
[0003] Thermally conductive gel is a new type of thermally conductive interface material. Conventional thermally conductive gel materials are generally composite materials made by directly mixing thermally conductive particles in organic polymer materials such as silicone oil. The addition of a large amount of thermally conductive fillers not only increases the cost and weight of the thermally conductive gel, but also reduces the interface wettability of the material, increases viscosity, and increases hardness, but it is difficult to significantly improve the thermal conductivity. Summary of the invention
[0004] The present invention is made in order to further improve the thermal conductivity of the thermally conductive gel.
[0005] As one aspect of the present invention, it relates to a composite thermally conductive filler, which is a graphene oxide-wrapped aluminum oxide composite thermally conductive filler, wherein the aluminum oxide is in-situ grown on the graphene surface. Generally speaking, in the implementation process of the present invention, spherical aluminum oxide is first in-situ grown on the two-dimensional graphene oxide surface. During the in-situ growth process, aluminum oxide has a bias and tends to grow on the same side of the graphene, while growing less on the other side. Then, during the spray drying process, it will curl up to form a form of graphene oxide-wrapped aluminum oxide, mostly in the form of microspheres. In the final product, aluminum oxide is basically located on the inner surface of the graphene.
[0006] Preferably, the microspheres have a diameter of 5 to 20 μm and a specific surface area of 1 to 5 m 2 / g.
[0007] Preferably, the graphene oxide is coupling agent-modified graphene. In a specific embodiment, the coupling agent is γ-aminopropyltriethoxysilane, a borate coupling agent, a titanate coupling agent or an aluminate coupling agent.
[0008] As another aspect of the present invention, it relates to a graphene in-situ modified thermally conductive gel, which contains the above-mentioned graphene oxide-wrapped aluminum oxide composite thermally conductive filler.
[0009] As another aspect of the present invention, it relates to a method for preparing the above-mentioned graphene oxide-wrapped aluminum oxide composite thermal conductive filler, comprising:
[0010] 1) Preparation of graphene oxide dispersion:
[0011] Dispersing graphite oxide in deionized water, adjusting the pH to between 4 and 7 (preferably 6 to 7) (adding ammonia water), preparing a graphite oxide suspension with a mass concentration of 1 to 20 g / L (preferably 5 to 10 g / L), exfoliating the graphite oxide suspension using a high-pressure homogenizer, and homogenizing (1 to 6 times) at a pressure of 30 to 80 MPa (preferably 40 to 60 MPa) to achieve monolayer exfoliation and a uniform and stable graphene oxide dispersion with a size of 5 to 20 μm;
[0012] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0013] The aluminum salt is dissolved in the graphene oxide dispersion, wherein the amount of the aluminum salt is 2 to 15 times the mass of the graphene oxide in terms of aluminum; the pH of the system is adjusted to between 8 and 12, and aluminum oxide particles are nucleated and in situ grown on the surface of the graphene oxide; spray drying is performed to obtain a graphene oxide dispersion having a size of 5 to 20 μm and a specific surface area of 1 to 5 m 2 / g of graphene oxide wrapped with aluminum oxide composite thermal conductive filler.
[0014] In a specific embodiment, in step 1), the pH is adjusted to between 6 and 7, and a graphite oxide suspension having a mass concentration of 5 to 10 g / L is prepared and homogenized under a pressure of 40 to 60 MPa.
[0015] In a specific embodiment, the aluminum salt is one of aluminum chloride, aluminum nitrate, aluminum sulfate, ammonium aluminum sulfate and sodium metaaluminate.
[0016] In a specific embodiment, in step 2), before spray drying, a coupling agent is added according to a mass ratio of the coupling agent to the graphene oxide of 1:5 to 1, and the reaction is carried out at 40 to 100° C. for 0.5 to 10 hours. In a specific embodiment, the coupling agent is γ-aminopropyltriethoxysilane, a borate coupling agent, a titanate coupling agent or an aluminate coupling agent.
[0017] In a specific embodiment, in step 2), the spray drying spray air pressure ranges from 2 to 20 MPa, and the outlet temperature ranges from 80 to 110°C.
[0018] As another aspect of the present invention, it relates to a method for preparing the above-mentioned graphene in-situ modified thermally conductive gel, comprising:
[0019] A platinum catalyst is dispersed in a silicone oil matrix, with the mass percentage of the platinum catalyst to the silicone oil being 0.1 to 2.0%; a thermally conductive filler of aluminum oxide wrapped in graphene oxide is dispersed in a silicone oil matrix (stirred at 1000 to 3000 rpm until uniformly mixed) according to a mass ratio of the graphene oxide-coated aluminum oxide composite thermally conductive filler to the silicone oil matrix of 10 to 15:1; and the graphene oxide is heated under vacuum conditions to vulcanize, crosslink and reduce the graphene oxide while maintaining mechanical stirring.
[0020] As another aspect of the present invention, it relates to the use of the above-mentioned composite thermally conductive filler in the preparation of graphene in-situ modified thermally conductive gel.
[0021] As another aspect of the present invention, it relates to the application of the above-mentioned graphene in-situ modified thermal conductive gel in the preparation of electronic products (such as mobile phones, communication base stations, new energy battery vehicles, LED chips, IGBT and other power modules, high-power semiconductors, aerospace, etc.).
[0022] As another aspect of the present invention, it relates to an electronic product, which includes the graphene in-situ modified thermally conductive gel as claimed in claim 13.
[0023] In the product prepared by the embodiment of the present invention, graphene and aluminum oxide balls are tightly coated. The present invention realizes the in-situ growth of aluminum oxide on the surface of graphene oxide by using aluminum salt and ammonia water in the graphene oxide dispersion, and also effectively inhibits the agglomeration of graphene oxide. In the drying stage, the spherical composite thermal conductive filler of aluminum oxide wrapped by graphene oxide is realized by spray drying, and the optimal spray droplet size is obtained by accurately controlling the pressure and outlet temperature range of the spray air. Under a smaller spray pressure, the droplet size is too large, resulting in the final composite thermal conductive filler size exceeding 20μm, and it is difficult for graphene to completely wrap aluminum oxide, so that the thermal conductivity of the thermal conductive gel obtained by this filler is low and the hardness is high; under a larger spray pressure, aluminum oxide will be separated from the surface of graphene oxide, resulting in uneven composite of graphene and aluminum oxide in the obtained composite filler. The special spherical graphene structure can effectively reduce the specific surface area of graphene (1 to 5m 2 / g), inhibiting large specific surface area graphene (theoretical specific capacity ~2600m 2 / g) The problem of large adsorption capacity of silicone oil matrix.
[0024] In the product prepared by the embodiment of the present invention, graphene is wrapped on the surface of alumina, and the two overlap and cooperate with each other to form a special compound effect of two-dimensional and zero-dimensional spheres, construct a three-dimensional and extensive thermal conductive network structure, and achieve high thermal conductivity and high extrusion rate at a lower filling amount.
[0025] The thermal conductivity of the product prepared in the embodiment of the present invention can reach 8 to 12 W / (m·K), and the extrusion rate exceeds 60 g / min. The process of the present invention is simple and easy to implement, suitable for industrial large-scale production, and improves the technical defect that the thermal conductivity of the graphene thermal conductive gel still does not reach 8 W / (m·K) after the existing cumbersome steps of preparation. DETAILED DESCRIPTION
[0026] The inventors prepared heat dissipation gels with reference to several prior art documents including CN108148558A, CN110003438A, CN105754350A and CN111471305A. The thermal conductivity of the prepared products could not exceed 8W / (m·K), which could not meet the inventors' expectations. After further research and development, the inventors made the present invention. The present invention develops a simple and easy process suitable for industrial large-scale production. The prepared high-performance graphene thermally conductive gel has a thermal conductivity of 8 to 12W / (m·K).
[0027] The inventors tried to mechanically mix graphene powder and aluminum oxide powder according to the prior art. However, due to the huge difference between the density of graphene powder (0.003 g / mL) and the density of aluminum oxide (3.96 g / mL), graphene and aluminum oxide are difficult to mix evenly, graphene is very easy to agglomerate, and it is difficult for graphene to form an effective path in the thermal conductive gel.
[0028] Based on the above, the inventors made the present invention after further research and development.
[0029] Source of raw materials or equipment:
[0030] Graphite oxide: The graphite oxide paste used has a solid content of 43±5wt%, a pH value of 1.8-2.3, a size ≤100μm, a carbon content of 51±5wt%, and a sulfur content ≤2wt%, and is SE2430W-N, a product of Changzhou Sixth Element Materials Technology Co., Ltd.
[0031] Evaluation and analysis method: Test equipment—DRL thermal conductivity meter, test method—ASTMD5470 thermal impedance thermal conductivity test standard.
[0032] Embodiment 1:
[0033] 1) Preparation of graphene oxide slurry
[0034] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0035] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0036] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0037] 3) Preparation of thermal conductive gel:
[0038] First, weigh 0.1g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 10g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 1000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 40rpm / min, heat it to 120℃ and react for 5h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 8.3W / (m·K) and the extrusion rate is 82g / min.
[0039] Embodiment 2:
[0040] 1) Preparation of graphene oxide slurry
[0041] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0042] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0043] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0044] 3) Preparation of thermal conductive gel:
[0045] First, weigh 2g of platinum catalyst and disperse it in 1g of dimethyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 12g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in dimethyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the dimethyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it at 80rpm / min, heat it to 200℃ and react for 0.5h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 9.5W / (m·K) and the extrusion rate is 72g / min.
[0046] Embodiment 3:
[0047] 1) Preparation of graphene oxide slurry
[0048] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0049] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0050] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0051] 3) Preparation of thermal conductive gel:
[0052] First, weigh 1g of platinum catalyst and disperse it in 1g of methylphenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 13g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the methylphenyl silicone oil, and stir it at a high speed of 3000rpm / min to evenly disperse the thermal conductive filler in the methylphenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 60rpm / min, heat it to 160℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 10.6W / (m·K) and the extrusion rate is 69g / min.
[0053] Embodiment 4:
[0054] 1) Preparation of graphene oxide slurry
[0055] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0056] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0057] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0058] 3) Preparation of thermal conductive gel:
[0059] First, weigh 2g of platinum catalyst and disperse it in 1g of methylchlorophenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in methylchlorophenyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the methylchlorophenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it at 80rpm / min, heat it to 200℃ and react for 1h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 12.1W / (m·K) and the extrusion rate is 63g / min.
[0060] Embodiment 5:
[0061] 1) Preparation of graphene oxide slurry
[0062] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0063] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0064] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0065] 3) Preparation of thermal conductive gel:
[0066] First, weigh 0.1g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 12.3W / (m·K) and the extrusion rate is 68g / min.
[0067] Embodiment 6:
[0068] 1) Preparation of graphene oxide slurry
[0069] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0070] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0071] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0072] 3) Preparation of thermal conductive gel:
[0073] First, weigh 0.2g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 12.1W / (m·K) and the extrusion rate is 65g / min.
[0074] Embodiment 7:
[0075] 1) Preparation of graphene oxide slurry
[0076] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0077] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0078] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0079] 3) Preparation of thermal conductive gel:
[0080] First, weigh 0.3g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 12.2W / (m·K) and the extrusion rate is 58g / min.
[0081] Embodiment 8:
[0082] 1) Preparation of graphene oxide slurry
[0083] Graphite oxide is dispersed in deionized water to prepare 1L of graphite oxide suspension with a mass concentration of 10g / L, a certain amount of ammonia solution is added, the pH is adjusted to 5, and the mixture is stirred evenly to obtain a graphite oxide dispersion; the graphene oxide dispersion is homogenized once under a pressure of 80MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide dispersion, wherein the size of the graphene oxide in the dispersion is 5μm.
[0084] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0085] First, 100 g of aluminum chloride was weighed and dissolved in 1 L of graphene oxide dispersion with a mass concentration of 10 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 9, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 2 g of γ-aminopropyltriethoxysilane was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 110 ° C to obtain a particle size of 5 μm and a specific surface area of 5.1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0086] 3) Preparation of thermal conductive gel:
[0087] First, weigh 0.5g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 12.1W / (m·K) and the extrusion rate is 55g / min.
[0088] Embodiment 9:
[0089] 1) Preparation of graphene oxide slurry
[0090] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 1 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized 3 times under a pressure of 30 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, and the size of the graphene oxide in the dispersion was 10 μm.
[0091] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0092] First, 140 g of aluminum sulfate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 1 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 12, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 5 g of borate coupling agent was added and reacted at 90 ° C for 0.5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 20 MPa and an outlet temperature of 100 ° C to obtain a particle size of 5 μm and a specific surface area of 4.9 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0093] 3) Preparation of thermal conductive gel:
[0094] First, weigh 0.1g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 11.6W / (m·K) and the extrusion rate is 65g / min.
[0095] Embodiment 10:
[0096] 1) Preparation of graphene oxide slurry
[0097] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 2 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 6, and the mixture was stirred evenly to obtain a graphite oxide dispersion. The graphene oxide dispersion was homogenized once under a pressure of 60 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 15 μm.
[0098] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0099] First, 300 g of aluminum nitrate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 2 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 11, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 5 g of titanate coupling agent was added and reacted at 80 ° C for 1 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 12 MPa and an outlet temperature of 100 ° C to obtain a particle size of 10 μm and a specific surface area of 2.3 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0100] 3) Preparation of thermal conductive gel:
[0101] First, weigh 0.1g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 11.7W / (m·K) and the extrusion rate is 61g / min.
[0102] Embodiment 11:
[0103] 1) Preparation of graphene oxide slurry
[0104] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 4 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized once at a pressure of 50 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 20 μm.
[0105] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0106] First, 400 g of ammonium aluminum sulfate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 4 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 10, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 5 g of aluminate coupling agent was added and reacted at 60 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 2 MPa and an outlet temperature of 80 ° C to obtain a particle size of 20 μm and a specific surface area of 1 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0107] 3) Preparation of thermal conductive gel:
[0108] First, weigh 0.1g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 11.9W / (m·K) and the extrusion rate is 63g / min.
[0109] Embodiment 12:
[0110] 1) Preparation of graphene oxide slurry
[0111] Graphite oxide was dispersed in deionized water to prepare 2L of graphite oxide suspension with a mass concentration of 5g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized twice under a pressure of 30MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 12μm.
[0112] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0113] First, 300 g of sodium aluminate was weighed and dissolved in 2 L of graphene oxide dispersion with a mass concentration of 5 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 12, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 5 g of aluminate coupling agent was added and reacted at 50 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with the spray air pressure range of 12 MPa and the outlet temperature of 90 ° C to obtain a particle size of 10 μm and a specific surface area of 3.2 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0114] 3) Preparation of thermal conductive gel:
[0115] First, weigh 0.1g of platinum catalyst and disperse it in 1g of vinyl silicone oil, and stir it mechanically until it is evenly dispersed; then weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in the vinyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the vinyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 10rpm / min, heat it to 200℃ and react for 2h to obtain a high-performance thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 11.7W / (m·K) and the extrusion rate is 65g / min.
[0116] Comparative Example 1
[0117] 3 g of intercalated graphene powder, 400 g of spherical alumina filler with an average particle size of 50 μm, 50 g of spherical alumina filler with an average particle size of 3 μm, and 100 g of a viscosity of 6000 mm 2 / s of dimethyl silicone oil is placed in a ball mill and stirred at 100 rpm for 10 minutes. 200g of zirconium oxide balls are added to the ball mill. The mixture is ball milled at 500 rpm for 20 hours. After the ball milling is completed, the mixture is taken out to obtain a thermally conductive gel composite material containing graphene. The test shows that the thermal conductivity of the thermally conductive gel is 5W / (m·K), and the extrusion rate is not measured.
[0118] Comparative Example 2
[0119] 1) Preparation of graphene oxide slurry:
[0120] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 4 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized once at a pressure of 50 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 20 μm.
[0121] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0122] First, 400 g of ammonium aluminum sulfate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 4 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 10, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; then, 5 g of aluminate coupling agent was added and reacted at 60 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by freeze drying to obtain a specific surface area of 155 m 2 / g of aluminum oxide loaded on graphene oxide lamellar composite thermal conductive filler.
[0123] 3) Preparation of thermal conductive gel:
[0124] First, weigh 2g of platinum catalyst and disperse it in 1g of methylchlorophenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 15g of the lamellar composite thermal conductive filler loaded on graphene oxide prepared in step 2 and disperse it in methylphenyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the methylchlorophenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 80rpm / min, heat it to 200℃ and react for 1h to obtain a thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 6W / (m·K) and the extrusion rate is 5g / min.
[0125] Comparative Example 3
[0126] 1) Preparation of graphene oxide slurry:
[0127] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 4 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized once at a pressure of 50 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 20 μm.
[0128] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0129] First, 400 g of commercial aluminum oxide spherical particles with a size of 5 μm were weighed and dispersed in 5 L of graphene oxide dispersion with a mass concentration of 4 g / L, and mechanically stirred until uniformly dispersed; then, 5 g of aluminate coupling agent was added and reacted at 60 ° C for 5 h to achieve the modification of aluminum oxide and graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 2 MPa and an outlet temperature of 80 ° C to obtain a spherical particle with a size of 20 μm and a specific surface area of 63 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0130] 3) Preparation of thermal conductive gel:
[0131] First, weigh 2g of platinum catalyst and disperse it in 1g of methylchlorophenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in methylphenyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the methylchlorophenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 80rpm / min, heat it to 200℃ and react for 1h to obtain a thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 7W / (m·K) and the extrusion rate is 13g / min.
[0132] Comparative Example 4
[0133] 1) Preparation of graphene oxide slurry:
[0134] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 4 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized once at a pressure of 50 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 20 μm.
[0135] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0136] First, 400 g of ammonium aluminum sulfate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 4 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 10, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 2 MPa and an outlet temperature of 80 ° C to obtain a particle size of 20 μm and a specific surface area of 1.2 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0137] 3) Preparation of thermal conductive gel:
[0138] First, weigh 2g of platinum catalyst and disperse it in 1g of methylchlorophenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in methylphenyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the methylchlorophenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 80rpm / min, heat it to 200℃ and react for 1h to obtain a thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 3W / (m·K) and the extrusion rate is 11g / min.
[0139] Comparative Example 5
[0140] 1) Preparation of graphene oxide slurry:
[0141] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 4 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized once at a pressure of 50 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 20 μm.
[0142] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0143] First, 400 g of ammonium aluminum sulfate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 4 g / L, and mechanically stirred until completely dissolved; then, ammonia water was added to adjust the pH to 10, and aluminum ions combined with hydroxide to achieve the nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 2 MPa and an outlet temperature of 80 ° C to obtain a particle size of 20 μm and a specific surface area of 1.2 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0144] 3) Preparation of thermal conductive gel:
[0145] First, weigh 2g of platinum catalyst and disperse it in 1g of methylchlorophenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, add 5g of aluminate coupling agent, weigh 15g of graphene oxide wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in methylphenyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in methylchlorophenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 80rpm / min, heat it to 200℃ and react for 1h to obtain thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 4.1W / (m·K) and the extrusion rate is 26g / min.
[0146] Comparative Example 6
[0147] 1) Preparation of graphene oxide slurry:
[0148] Graphite oxide was dispersed in deionized water to prepare 5 L of graphite oxide suspension with a mass concentration of 4 g / L, a certain amount of ammonia solution was added, the pH was adjusted to 7, and the mixture was stirred evenly to obtain a graphene oxide dispersion. The graphene oxide dispersion was homogenized once at a pressure of 50 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphite oxide dispersion, wherein the size of the graphene oxide in the dispersion was 20 μm.
[0149] 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler:
[0150] First, 400 g of ammonium aluminum sulfate was weighed and dissolved in 5 L of graphene oxide dispersion with a mass concentration of 4 g / L, and mechanically stirred until completely dissolved; then, 5 g of aluminate coupling agent was added and stirred until dissolved; then, ammonia water was added to adjust the pH to 10, and aluminum ions combined with hydroxide to achieve nucleation of aluminum oxide particles and in-situ growth on the surface of graphene oxide; finally, the mixed system was dried by spray drying method, with a spray air pressure of 2 MPa and an outlet temperature of 80 ° C to obtain a particle size of 20 μm and a specific surface area of 1.2 m 2 / g coupling agent modified graphene oxide wrapped alumina composite thermal conductive filler.
[0151] 3) Preparation of thermal conductive gel:
[0152] First, weigh 2g of platinum catalyst and disperse it in 1g of methylchlorophenyl silicone oil, and stir it mechanically until it is evenly dispersed; then, weigh 15g of the graphene oxide-wrapped aluminum oxide composite thermal conductive filler prepared in step 2 and disperse it in methylphenyl silicone oil, and stir it at a high speed of 2000rpm / min to evenly disperse the thermal conductive filler in the methylchlorophenyl silicone oil; finally, transfer the system to a planetary mixer, evacuate it to vacuum at 80rpm / min, heat it to 200℃ and react for 1h to obtain a thermal conductive gel. Tests show that the thermal conductivity of the thermal conductive gel is 3.5W / (m·K) and the extrusion rate is 13g / min.
[0153] The properties of the graphene thermally conductive gels prepared in Examples 1 to 5 were compared with those prepared in Comparative Example 1. The thermal conductivity of the thermally conductive gel prepared in Example 4 can reach 12 W / (m·K), which is much higher than 5 W / (m·K) in Comparative Example 1. At the same time, the extrusion rate exceeds 60 g / min and can reach up to 82 g / min.
[0154] The properties of the graphene thermally conductive gels prepared in Examples 1 to 5 were compared with those prepared in Comparative Example 2. The thermal conductivity of the thermally conductive gel prepared in Example 4 can reach 12W / (m·K), which is much higher than the 6W / (m·K) of Comparative Example 2. At the same time, the extrusion rate exceeds 60g / min, which is much higher than the 5g / min of Comparative Example 2. The main difference between Comparative Example 2 and the embodiment is that freeze drying is used instead of spray drying. The freeze drying method is to freeze the system into a solid, and then use the principle of sublimation of ice under low pressure to perfectly retain the two-dimensional lamellar structure of graphene. Therefore, the specific surface area of the alumina-loaded graphene oxide composite filler obtained in Comparative Example 2 is as high as 155m 2 / g, much higher than 1.1m / g in Example 4 2 / g, such a high specific surface area is dispersed in methylphenyl silicone oil, and the methylphenyl silicone oil will quickly adsorb on the large area of graphene surface, making it difficult for the silicone oil to evenly wet all the fillers and form a uniform and highly extrudable thermal conductive gel.
[0155] The properties of the graphene thermally conductive gels prepared in Examples 1 to 5 were compared with those prepared in Comparative Example 3. The thermal conductivity of the thermally conductive gel prepared in Example 4 can reach 12W / (m·K), which is much higher than the 7W / (m·K) of Comparative Example 3. At the same time, the extrusion rate exceeds 60g / min, which is much higher than the 13g / min of Comparative Example 2. The main difference between Comparative Example 3 and the embodiment is that commercial micron aluminum oxide is used. The density of aluminum oxide is as high as 3.96g / mL. It is difficult to evenly disperse it in the dispersion of graphene oxide by mechanical stirring, so it is difficult to evenly disperse it on the surface of graphene oxide. In the composite filler obtained by spray drying, most of the aluminum oxide particles are not compounded with graphene. Graphene oxide is wrapped and dried into a sphere alone. Aluminum oxide is dried into a powder in its initial state. Therefore, the specific surface area of the composite filler is still as high as 63m 2 / g, which makes it difficult for silicone oil to evenly wet all the fillers and form a uniform and highly extrudable thermal conductive gel.
[0156] The properties of the graphene thermally conductive gels prepared in Examples 1 to 5 were compared with those prepared in Comparative Example 4. The thermal conductivity of the thermally conductive gel prepared in Example 4 can reach 12W / (m·K), which is much higher than 3W / (m·K) of Comparative Example 4. At the same time, the extrusion rate exceeds 60g / min, which is much higher than 11g / min of Comparative Example 4. The main difference between Comparative Example 4 and the embodiment is that the composite thermally conductive filler is not modified by the coupling agent, resulting in poor compatibility of the graphene-wrapped alumina thermally conductive filler with silicone oil during the preparation of the thermally conductive gel, and it is difficult to evenly disperse in the silicone oil. Therefore, it is difficult to form a thermally conductive network structure, the thermal conductivity is low, and the extrusion rate is also low.
[0157] The properties of the graphene thermally conductive gel prepared in Examples 1 to 5 were compared with those of the graphene thermally conductive gel prepared in Comparative Example 5. The thermal conductivity of the thermally conductive gel prepared in Example 4 can reach 12W / (m·K), which is much higher than 4.1W / (m·K) of Comparative Example 5. At the same time, the extrusion rate exceeds 60g / min, which is much higher than 26g / min of Comparative Example 5. The main difference between Comparative Example 5 and the embodiment is that the silane coupling agent is added during the preparation of the thermally conductive gel, and is added to the silicone oil matrix at the same time as the thermally conductive filler, without the thermally conductive filler being modified specifically before. The coupling agent modification needs to react at a certain temperature, and the mixing process of the thermally conductive filler and the silicone oil is carried out at room temperature. Therefore, it is difficult for the coupling agent to be effectively grafted on the surface of the thermally conductive filler, resulting in poor compatibility between the thermally conductive filler and the silicone oil, and it is difficult to be evenly dispersed in the silicone oil. Therefore, it is difficult to form a thermally conductive network structure, the thermal conductivity is low, and the extrusion rate is also low.
[0158] The properties of the graphene thermally conductive gels prepared in Examples 1 to 5 were compared with those prepared in Comparative Example 5. The thermal conductivity of the thermally conductive gel prepared in Example 4 can reach 12W / (m·K), which is much higher than 3.3W / (m·K) of Comparative Example 6. At the same time, the extrusion rate exceeds 60g / min, which is much higher than 13g / min of Comparative Example 6. The main difference between Comparative Example 6 and the embodiment is that the silane coupling agent is added before the formation of alumina, the coupling agent modification needs to react at a certain temperature, and the subsequent preparation of aluminum oxide and graphene encapsulation process does not have a high temperature process; moreover, in the subsequent drying process, the coupling agent is partially adsorbed on the surface of alumina, but not adsorbed on the surface of graphene. Therefore, it is difficult for the coupling agent to be effectively grafted on the surface of graphene, resulting in poor compatibility of the thermally conductive filler with silicone oil, and it is difficult to be evenly dispersed in silicone oil. Therefore, it is difficult to form a thermally conductive network structure, the thermal conductivity is low, and the extrusion rate is also low.
Claims
1. A composite thermally conductive filler, characterized in that: The composite thermal conductive filler is a composite thermal conductive filler of aluminum oxide wrapped in graphene oxide, wherein aluminum oxide is in-situ grown on the surface of graphene oxide, and the composite thermal conductive filler is microspheres of the composite thermal conductive filler of aluminum oxide wrapped in graphene oxide.
2. The composite thermally conductive filler according to claim 1, characterized in that: The aluminum oxide is in-situ grown on the inner surface of the graphene oxide.
3. The composite thermally conductive filler according to claim 1, characterized in that: The microspheres have a diameter of 5 to 20 μm and a specific surface area of 1 to 5 m 2 / g.
4. The composite thermally conductive filler according to any one of claims 1 to 3, characterized in that: The graphene oxide is coupling agent modified graphene.
5. The composite thermally conductive filler according to claim 4, characterized in that: The coupling agent is γ-aminopropyltriethoxysilane, a borate coupling agent, a titanate coupling agent or an aluminate coupling agent.
6. A method for preparing the composite thermally conductive filler according to any one of claims 1 to 5, characterized in that: include: 1) Preparation of graphene oxide dispersion: The graphite oxide is dispersed in deionized water, and the pH is adjusted to between 4 and 7 to prepare a graphite oxide suspension with a mass concentration of 1 to 20 g / L. The graphite oxide suspension is exfoliated by a high-pressure homogenizer, and homogenized at a pressure of 30 to 80 MPa to achieve monolayer exfoliation and a uniform and stable graphene oxide dispersion with a size of 5 to 20 μm. 2) Preparation of graphene oxide wrapped aluminum oxide composite thermal conductive filler: The aluminum salt is dissolved in the graphene oxide dispersion, wherein the amount of the aluminum salt is 2 to 15 times the mass of the graphene oxide in terms of aluminum; the pH of the system is adjusted to between 8 and 12, and aluminum oxide particles are nucleated and in situ grown on the surface of the graphene oxide; spray drying is performed to obtain a graphene oxide dispersion having a size of 5 to 20 μm and a specific surface area of 1 to 5 m 2 / g of graphene oxide wrapped with aluminum oxide composite thermal conductive filler.
7. The method of claim 6, characterized in that In step 1), the pH is adjusted to between 6 and 7, and a graphite oxide suspension having a mass concentration of 5 to 10 g / L is prepared and homogenized under a pressure of 40 to 60 MPa.
8. The method of claim 6, characterized in that The aluminum salt is one of aluminum chloride, aluminum nitrate, aluminum sulfate, ammonium aluminum sulfate and sodium metaaluminate.
9. The method of claim 6, characterized in that In step 2), before spray drying, a coupling agent is added according to a mass ratio of the coupling agent to the graphene oxide of 1:5 to 1, and the reaction is carried out at 40 to 100° C. for 0.5 to 10 hours.
10. The method according to claim 9, characterized in that The coupling agent is γ-aminopropyltriethoxysilane, a borate coupling agent, a titanate coupling agent or an aluminate coupling agent.
11. The method of claim 6, characterized in that In step 2), the spray drying spray air pressure ranges from 2 to 20 MPa, and the outlet temperature ranges from 80 to 110°C.
12. A graphene in-situ modified thermally conductive gel, characterized in that: Contains the composite thermally conductive filler according to any one of claims 1 to 5.
13. A method for preparing the graphene in-situ modified thermally conductive gel according to claim 12, comprising: The platinum catalyst is dispersed in the silicone oil matrix, and the thermal conductive filler is dispersed in the silicone oil matrix according to a mass ratio of the composite thermal conductive filler to the silicone oil matrix of 10 to 15:1; While maintaining mechanical stirring, the graphene oxide is heated, sulfurized, cross-linked and reduced under vacuum conditions.
14. The method of claim 13, characterized in that The mass percentage of the platinum catalyst and the silicone oil is 0.1-2.0%.
15. An electronic product, characterized in that: The electronic product comprises the graphene in-situ modified thermally conductive gel according to claim 12.
Citation Information
Patent Citations
High-heat-conductivity gel sheet and preparation method thereof
CN105754350A
Preparation method of highly dispersed graphene-based thermal conductive silica gel
CN109294236A
Method for carrying out replacement of an upperstructure of a bridge
KR102247200B1
Graphene-Based Composite and Method of Preparing the Same
US20140183415A1
Cited By
Preparation method of carboxylated cellulose nanofiber (CCNF) and reduced graphene oxide-based directional high-thermal-conductivity aerogel-based composite phase change material
CN122302359A